Pratique # 17 : Les séances de dialogue au Réseau de santé Horizon (Nouveau-Brunswick) - Benoît, Josée; Dagnogo, Djenaba Sarah; Savard, Jacinthe; Savard, Sébastien (Dans: GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire., 2021)
Le Réseau de santé Horizon est la plus grande régie régionale de la santé au Nouveau-Brunswick. La langue de travail dans les établissements de ce réseau est généralement l’anglais, mais les services qui y sont dispensés doivent être offerts dans les deux langues officielles, comme l'exige la loi sur les langues officielles du Nouveau-Brunswick. Cherchant des moyens d’améliorer les pratiques d’offre active au sein de ses établissements, le réseau a réalisé qu'il fallait s'assurer de l'adhésion des gestionnaires et du personnel à cet objectif. Les séances de dialogue visaient donc à créer des échanges entre le personnel du Réseau afin d’obtenir des commentaires, des opinions et des recommandations qui favoriseraient l’adhésion aux pratiques d’offre active et à l’amélioration de la qualité des services en français. Les données recueillies pendant les séances serviraient à initier des pratiques plus concrètes visant à mieux outiller les employés afin qu’ils puissent offrir des services dans les deux langues officielles.

Perceptions des professionnels de la santé quant aux besoins oncologiques pédiatriques offerts en français à domicile : étude descriptive qualitative - Chartrand, Julie; Jibb, Lindsay; Grandmont, Camille; Hardy-Bélanger, Élisabeth; Cheng, Sara; Balasa, Rebecca; Johnston, Donna (Revue canadienne de soins infirmers en oncologie, 2022)

Assessment Report of the Café de Paris Initiative and its Impact in New Brunswick. - Consortia and Associate.s (Société Santé et Mieux-être en français du Nouveau-Brunswick, 2021)

L'effectivité des lois linguistiques dans le secteur de la santé - Forgues, Éric; Maillet, Stéphanie (Minorités linguistiques et société / Linguistic Minorities and Society, 2024)
Cet article découle d’une étude qui problématise le concept d’effectivité des lois linguistiques. Dans cette étude, nous cherchions à mieux comprendre les dimensions juridiques, sociales, organisationnelles et psychologiques qui peuvent agir sur l’effectivité des lois linguistiques dans le secteur de la santé dans les provinces du Canada qui disposent de telles lois. Sachant que les professionnels de la santé sont en première ligne pour offrir des services en français, nous avons analysé leurs perceptions en ce qui concerne divers aspects pouvant influencer l’offre de services en français. Les résultats montrent que des différences souvent significatives s’observent entre les répondantes et les répondants anglophones et francophones et ceux qui oeuvrent dans des hôpitaux anglophones et francophones. Les résultats révèlent également que des efforts doivent se poursuivre pour atteindre une effectivité accrue, tout en offrant des pistes pour mieux orienter ces efforts. Mots-clés : effectivité des lois linguistiques, santé en français, francophonie, langue de service, minorités linguistiques

L'effectivité des lois linguistiques dans le secteur de la santé. Rapport - Forgues, Éric; Maillet, Stéphanie; Morin, Philippe; Doucet, Michel (Institut canadien de recherche sur les minorités linguistiques, 2020)

L'effectivité des lois linguistiques dans le secteur de la santé. Sommaire - Forgues, Éric; Maillet, Stéphanie; Morin, Philippe; Doucet, Michel (Institut canadien de recherche sur les minorités linguistiques, 2020)

Creating a Culture of Active Offer in Both Official Languages: A Case Study of a Dialogue - Forgues, Éric; Paulin, Christine C. (Minorités linguistiques et société / Linguistic Minorities and Society, 2024)
Abstract To establish a culture of active service provision (AO) in both official languages, Horizon Health Network in New Brunswick conducted dialogue sessions involving over 3,400 employees. These discussions enabled participants to express their opinions on AO, the challenges encountered, and potential solutions. Our project aimed to gain a better understanding of the impact of dialogue activities on the development of an AO culture within the Horizon Health Network. Analysis of the evaluations conducted after each session, internal documentation, and interviews with eight organizers and facilitators of these dialogues, indicate that this type of exercise has the potential to establish an AO culture while also providing insights into certain obstacles. Keywords: health in French, service language, active offer, organizational culture, linguistic skills of organizations Résumé Afin d’implanter une culture de l’offre active (OA) des services dans les deux langues officielles, le réseau de santé Horizon au Nouveau-Brunswick a mené des sessions de dialogues auprès de plus de 3 400 employés. Ces dialogues ont permis aux participantes et aux participants d’exprimer leurs opinions sur l’OA, les défis rencontrés et des pistes de solution. Notre projet visait à mieux comprendre la portée des activités de dialogue sur le développement d’une culture de l’OA au sein du réseau de santé Horizon. L’analyse des évaluations réalisées après chacune des sessions, de la documentation interne et des entretiens menés auprès de huit organisatrices et animatrices de ces dialogues, montre que ce type d’exercice recèle un potentiel pour mettre en place une culture de l’OA, tout en permettant de mieux comprendre certains blocages. Mots-clés : santé en français, langue de service, offre active, culture organisationnelle, compétences linguistiques des organisations

Vers une culture de l’offre active de services de santé dans les deux langues officielles, étude de cas d’une pratique de dialogue. - Forgues, Éric; Paulin, Christine C. (Minorités linguistiques et société / Linguistic Minorities and Society, 2024)
Résumé Afin d’implanter une culture de l’offre active (OA) des services dans les deux langues officielles, le réseau de santé Horizon au Nouveau-Brunswick a mené des sessions de dialogues auprès de plus de 3 400 employés. Ces dialogues ont permis aux participantes et aux participants d’exprimer leurs opinions sur l’OA, les défis rencontrés et des pistes de solution. Notre projet visait à mieux comprendre la portée des activités de dialogue sur le développement d’une culture de l’OA au sein du réseau de santé Horizon. L’analyse des évaluations réalisées après chacune des sessions, de la documentation interne et des entretiens menés auprès de huit organisatrices et animatrices de ces dialogues, montre que ce type d’exercice recèle un potentiel pour mettre en place une culture de l’OA, tout en permettant de mieux comprendre certains blocages. Mots-clés : santé en français, langue de service, offre active, culture organisationnelle, compétences linguistiques des organisations Abstract To establish a culture of active service provision (AO) in both official languages, Horizon Health Network in New Brunswick conducted dialogue sessions involving over 3,400 employees. These discussions enabled participants to express their opinions on AO, the challenges encountered, and potential solutions. Our project aimed to gain a better understanding of the impact of dialogue activities on the development of an AO culture within the Horizon Health Network. Analysis of the evaluations conducted after each session, internal documentation, and interviews with eight organizers and facilitators of these dialogues, indicate that this type of exercise has the potential to establish an AO culture while also providing insights into certain obstacles. Keywords: health in French, service language, active offer, organizational culture, linguistic skills of organizations

Exploring Primary Care Physicians’ Experiences of Language and Cultural Discordant Care for Linguistic Minority Patients at the End-of-Life: A Study Protocol - Lee, Seung Heyck; Gibb, Maya; Karunananthan, Sathya; Cody, Margaret; Tanuseputro, Peter; Johnston, Sharon; Kendall, Claire; Bedard, Daniel; Collin, Stéphanie; Kehoe MacLeod, Krystal (International Journal of Qualitative Methods, 2023)
Health disparities exist across different linguistic groups. Language barriers in primary care can negatively affect access to healthcare services and the quality and safety of care at the end-of-life. This study will take a novel, in-depth look at the experience of language- and/or cultural-discordant care for adults from linguistic minority groups through the eyes of primary care physicians providing palliative and/or end-of-life care. Language and cultural discordance means that the physician and patient do not speak the same language or are not from the same cultural background. Qualitative data from primary care physicians (n = 12–24) providing language-discordant end-of-life care to Francophone and/or Allophone older adults across different care models and diverse geographies in Ontario will be collected through semi-structured interviews. Reflexive thematic analysis will be used to report themes within the data and consider the influence of the social locations of the researcher and research participants, geographic considerations impacting service provision, and barriers imposed by differing primary care funding structures on the provision of palliative and end-of-life care for linguistic and cultural minority groups in Ontario. Findings from this study will identify the interconnections among language and cultural discordance, care model, geographic region, and physician perceptions of their combined effects on access to, and quality of, palliative and end-of-life care. This evidence will be key to informing clinical practice guidelines and mobilizing change to improve primary care access and quality for adults at the end-of-life from linguistic and cultural minority populations across Ontario. Keywords: language discordance, qualitative research, reflexive thematic analysis, palliative care, primary care physicians, semi-structured interviews

Official Language Minority Communities in Ontario: Understanding the Lived Experiences of Francophone Patients and their Nursing Care Providers - Muray, Mwali (Université d'Ottawa/University of Ottawa, 2022)
Although Canada is a bilingual country, official language minority community patients struggle to access quality care in their language. This reality has been of concern for Francophone minority communities in Ontario, but has seldom been examined in a nursing context. This research sought to examine the lived experiences of registered nurses and nursing students providing care to French-speaking patients in Ontario, as well as the realities of Francophone patients seeking French language health care services in Ontario. The conceptual frameworks guiding the study were the “Four Levels of Change for Improving Quality” model and the “Four-Level Model of the Health Care System.” Using qualitative phenomenological inquiry, as influenced by Martin Heidegger and Max van Manen, 31 semi-structured interviews were conducted with three subsets (n=10 Francophone patients; n=10 nursing students; n=11 registered nurses) throughout Ontario who had experience with the phenomenon being investigated. Data collection took place over a year (2018-2019) and was analysed thematically. Significant findings were identified across the three groups. Participants revealed the patchwork of individual actions taking place to remedy the existing gaps regarding care for Francophone minority populations. This included navigating a health care system where good enough care was the unfortunate standard for Francophone patients, and discussing how Francophone patients and nursing care providers implement strategies individually to manage the lack of resources for Francophone patient populations in Ontario. This thesis asserts that official language minority communities and their nursing care providers remain faced with difficulties providing and receiving care in Ontario. While numerous structures and resources exist to remediate the problems, these interventions and resources are not always implemented systemically, leading to a disproportionate burden on individuals, significant risks for safety for patient populations, and ethical dilemmas for nursing care providers. Recommendations are provided to bridge the gaps and ensure considerations of the needs of linguistic minorities throughout the health care system. Keywords: Francophonie, Linguistic Minorities, Nursing, Phenomenology, Qualitative Research

Official Language Minority Communities in Ontario: (In)visibility of Nursing Care - Muray, Mwali; Chartrand, Julie; Perron, Amélie (Aporia, 2026)
Despite Canada’s linguistic duality, French-speaking minority populations continue to face significant barriers in accessing equitable health care. Investigating two key research questions, this study explores: (1) What are the lived experiences of registered nurses and nursing students caring for French-speaking patients in Ontario? and (2) How do French-speaking patients navigate the health care system to access care in their preferred language? Using qualitative methodology informed by interpretive phenomenology, 31 participants were interviewed individually between 2018 and 2019, offering firsthand accounts of their experiences. Findings reveal a paradox of (in)visibility: French-speaking patients and nursing providers remain invisible when they adapt to systemic shortcomings but become highly visible when they advocate for equitable care. The study highlights the urgent need for the effective and consistent implementation of the strategic changes within health care institutions. Addressing these linguistic disparities is not only a matter of patient safety and quality care but also a fundamental step toward upholding Canada’s bilingual commitments in health service delivery.

Reporting on knowledge, attitudes, and behaviours of pharmacists regarding the active offer of French language health services in Ontario: A quantitative survey study - Timony, Patrick; Leone, Arielle; Caron, Carolanne; Giguère, Pierre; Thabet, Pierre; Gauthier, Alain; Waite, Nancy M.; Landry, Christine (Canadian Pharmacists Journal / Revue des Pharmaciens du Canada, 2025)
Background: Patient–provider language discordances can negatively affect the availability, accessibility, acceptability, and quality (AAAQ) of pharmacy services as described by the AAAQ framework. With nearly 600,000 residents of Ontario identifying French as their mother tongue, the active offer (AO) of French language pharmacy services should be provided, yet little is known about pharmacists’ familiarity and use of AO. Methods: Ontario pharmacists completed an online survey measuring their knowledge, attitudes, and behaviours (KAB) regarding the AO for French language services (FLS). Demographics, including ability to converse in French, were collected. KAB AO scores were calculated and compared using descriptive and inferential statistics. Results: A total of 360 pharmacists completed the survey. The majority (65.1%) practiced in a primary care setting, 21.1% spoke French, and 71.8% lived in an area where less than 10% of the population were Francophone. Overall, AO scores were highest for attitude (3.8/5) and lowest for behaviours (2/5) and knowledge (1.8/5). Most pharmacists (62.8%) indicated an interest in AO training. Discussion: Gaps in KAB regarding AO for FLS by Ontario pharmacists resemble those observed throughout the health care system. Further training is suggested to address the lack of knowledge regarding AO, particularly its proactive nature, as well as strategies for its implementation. Conclusion: Although most participating pharmacists demonstrated gaps in AO knowledge and behaviour, many had favourable attitudes toward the importance of AO in the pharmacy setting and agreed that further training would be needed to improve their KAB. Further, the AO can address all 4 elements of the AAAQ framework.

Expériences en foyers de soins de longue durée et enjeux linguistiques en Ontario : Perspectives d’aîné·es francophones, de proches aidant·es, d’intervenant·es et de gestionnaires. Rapport de recherche - van Kemenade, Solange; Benoît, Josée; Bouchard, Louise; Sauvé-Schenk, Katrine; Savard, Jacinthe (Chaire de recherche de l’Université d’Ottawa et de l’Institut du savoir Montfort sur la santé des francophones de l’Ontario (2019-2024), Université d’Ottawa, 2025)
L’étude rapportée dans ce rapport visait à cerner la disponibilité de services en français dans les FSLD, leur accès, ainsi que l’impact de barrières linguistiques sur la santé et le bien-être, la qualité et la sécurité de soins à partir des perspectives des gestionnaires, des intervenant·es et des personnes résidant dans un FSLD ou de leur proche aidant·e. Elle cherchait également à explorer les variations dans l’offre de services en français en fonction du statut linguistique des foyers, qu’ils soient à caractère francophone, désignés, identifiés ou non identifiés. Ce rapport intégral présente des résultats détaillés, accompagnés de plusieurs citations de participants.

Expériences en foyers de soins de longue durée et enjeux linguistiques en Ontario : Perspectives d’aîné·es francophones, de proches aidant·es, d’intervenant·es et de gestionnaires. Rapport de synthèse - van Kemenade, Solange; Benoît, Josée; Bouchard, Louise; Sauvé-Schenk, Katrine; Savard, Jacinthe (Chaire de recherche de l’Université d’Ottawa et de l’Institut du savoir Montfort sur la santé des francophones de l’Ontario (2019-2024), Université d’Ottawa, 2025)
L’étude rapportée dans ce rapport de synthèse visait à cerner la disponibilité de services en français dans les FSLD, leur accès, ainsi que l’impact de barrières linguistiques sur la santé et le bien-être, la qualité et la sécurité de soins à partir des perspectives des gestionnaires, des intervenant·es et des personnes résidant dans un FSLD ou de leur proche aidant·e. Elle cherchait également à explorer les variations dans l’offre de services en français en fonction du statut linguistique des foyers, qu’ils soient à caractère francophone, désignés, identifiés ou non identifiés. Ce rapport de synthèse en décrit les principaux constats, accompagnés de quelques citations de participants.